HISTORICAL APPROACH AND SOURCES OF INFORMATION FOR RETROSPECTIVE GEOMORPHOLOGICAL MAPPING OF URBANIZED AREAS. - Rodrigues, Cleide; da Luz, Rodolfo Alves; Moroz Caccia-Gouveia, Isabel Cristina [UNESP]; Veneziani, Yuri; Simas, Iury Tadashi Hirota; Carvalho, Deborah (Derbyana, 2024)
This paper presents the procedures of the historical approach in geomorphology and the unusual sources of information recommended by this, as well as the basic elements for detailed retrospective geomorphological mapping of urbanized areas. Retrospective cartography consists of identifying and representing the original morphology (preurbanization phase), and the sequence of interventions on surface forms and materials, offering an important tool for identifying and interpreting changes in processes. It is presented examples of mapping and ways of using cartographic information for later dimensioning of effects and impacts of anthropic interventions in river systems in the city of São Paulo. These studies used mainly current and old topographic maps, old and more up-to-date aerial photographs, field observations and measurements, neighborhood newspapers, photographic records, paintings, technical reports, surveys, interviews with former residents or key people related to various institutions, reports from naturalists, among other sources of information partly recommended by authors who work with historical geomorphology. The mappings identify relevant intervention phases or historical stages of disturbance, called: pre-urban stage, active disturbance stage and post-disturbance stage, are also presented. It was possible to demonstrate that cities with relatively modern urbanization such as São Paulo have the potential for the use of historical sources to recover precise geographic information about the physical environment, especially old maps and aerial photographs that reveal pre-urban conditions with a high level of precision, particularly for a trained geomorphologist. Finally, it is demonstrated how certain more advanced technological instruments can be allies within this perspective of using historical and retrospective sources.
ENFOQUE HISTÓRICO Y FUENTES DE INFORMACIÓN PARA LA CARTOGRAFÍA GEOMORFOLÓGICA RETROSPECTIVA DE ZONAS URBANIZADAS.
ABORDAGEM HISTÓRICA E FONTES DE INFORMAÇÃO PARA O MAPEAMENTO GEOMORFOLÓGICO RETROSPECTIVO DE ÁREAS URBANIZADAS
Keywords: Anthropocene; Geomorphological Cartography; Historical sources; Urban Geomorphology